Java RMI in a Mobile Environment - MacSweeney, Paul (Trinity College Dublin. Department of Computer Science, 2004)
There are many problems that must be addressed when attempting to enhance a particular middleware programming framework, in this case Java RMI, to allow it operate effectively in a mobile environment. The Architecture for Location Independent Computing Environments provides for the addition of mobility to such a framework in a set of reusable components. In this thesis I have outlined the problems that Java RMI faces and have implemented the components to allow it operate under mobile conditions. Using a layered approach, I tackled common mobility issues like disconnection, relocation and reference managementw ith specific reference to Sun Microsystems' implementation of Java RMI. I have provided a detailed design and implementation written in Java while also utilizing an enhanced version of the standard Berkeley sockets API with the Java Native Interface. This updated API now facilitates the creation of mobile friendly RMI applications and can be utilized with the maximum amount of transparency available to the application programmer. The platform used to implement the design was JBuilderX running on Fedora Core Linux.
Keywords: Computer Science